Carbonyl oxide chemistry in water cluster: An extended computational study. Issue 23 (29th July 2020) - Kashyap, Chayanika; Baruah, Indrani; Rohman, Shahnaz S.; Ullah, Sabnam S.; Kalita, Amlan J.; Borgohain, Gargi; Guha, Ankur K.
Abstract: An extended computational approach has been utilized to explore the reactions of acids with carbonyl oxide, also known as Criegee intermediate (CI). The reactions were explored inside a water cluster containing 50 water molecules. All possibilities of product formation were considered. Among the considered acids, the rate of 1, 4‐insertion follows the order HCOO < HCl < HNO3 . The most stable products of the reactions between the considered acids and CI have been identified. Abstract : An extensive computational study has been carried out to investigate the reaction of Crieege Intermediate with different acids within water cluster.